Assessing economic value added by university-based new-venture outreach programs - McMullan, W.Ed; Long, Wayne A.; Graham, James B. (Journal of Business Venturing, 1986)
A new-venture development office was set up in a university to solicit, screen, and allocate community ventures into upper-level undergraduate and graduate project courses. Innovative ventures in the early stages of development were allocated according to: 1) the project requirements of different courses and 2) the assessed needs of the ventures themselves. During 1984, 89 different projects with a weighted average of 125 manhours per project were run through the new-venture office. Students who conducted the projects included law students, industrial-design students, and a few undergraduate commerce students, although the majority of the work was done by second-year MBA students. Most of the MBA students were parttime students holding middle-management positions and having five or more years of relevant business experience. Projects were run through twelve different courses and a seed-capital conference. The program was conceptualized and coordinated by a number of professors teaching within an entrepreneurship concentration in an MBA program. Early in 1985, a telephone survey of 50 of the 63 entrepreneurs who had projects in the program was completed. These people were asked to systematically and realistically assess the resulting net benefits to their ventures along a number of different prespecified dimensions. The total value added was computed to be $1.75 million (CDN). which stands in contrast to the direct, out-of-pocket cost of the program, which was only $75,000 (CDN). The individual dimensions of value added that were measured included: •• Time gained or saved in advancing their new venture;•• Knowledge (understanding) gained of new-venture development;•• Information added of use in pursuing their new venture;•• Contacts made in support of their new venture;•• Strategic changes made; and•• Overall value of the experience. Additionally, respondents were asked to report whether or not they had secured new capital injections, increased or decreased employee levels, or made structural advances in their ventures. Rather than assume that the program was the primary instigator of all such changes, the respondents were asked to assess the relative impact of the program along appropriate dimensions. The program was perceived to have had a significant influence on most of the dimensions measured. A summary of the major results includes: •• Average value added of time saved or gained: $6,097.50;•• Average valeu added of new knowledge about venture development: $9, 389.47;•• Average value added of new information added: $6,293.48;•• Average value added of new contracts made: $7, 238.89;•• Average value added of strategy changes: $16,937.50;•• Average value added of overall involvement in the program: $37,269.00;•• Net employment generated: 20.4 FTE; and•• New capital raised: $5.1 million. Certain shortcomings of the research are discussed, including the validity and reliability of the value added measures. Research is continuing to validate the findings and refine the program.